2017
DOI: 10.4172/2254-609x.100079
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neuroprotective Effects of Neurotropin in Cultured Rat Dorsal Root Ganglion Neurons Using High- Throughput Imaging

Abstract: Background: Neurotropin, a non-protein extract derived from inflamed rabbit skin following inoculation with vaccinia virus, is an analgesic agent. The mechanism of action of neurotropin has been partially clarified. No experimental study, however, has been undertaken to assess oxaliplatin-induced neurotoxicity using quantitative in vitro high-throughput image analysis. In the present study, to elucidate the action of neurotropin on dorsal root ganglion (DRG) neurons, we explored the antioxidative and anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Neurotropin (NTP) is a drug derived from the non-protein fraction extracted from the inflamed skin of rabbits after vaccinia virus administration [1,[16][17][18][19][20][21][22]. NTP has been safely used in Japan for more than 50 years to treat various chronic pain conditions, such as lower back pain, cervico-omo-brachial syndrome, postherpetic neuralgia, hyperesthesia of subacute myelo-optic neuropathy, and other painful conditions [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotropin (NTP) is a drug derived from the non-protein fraction extracted from the inflamed skin of rabbits after vaccinia virus administration [1,[16][17][18][19][20][21][22]. NTP has been safely used in Japan for more than 50 years to treat various chronic pain conditions, such as lower back pain, cervico-omo-brachial syndrome, postherpetic neuralgia, hyperesthesia of subacute myelo-optic neuropathy, and other painful conditions [23].…”
Section: Introductionmentioning
confidence: 99%
“…NTP significantly reduced bidirectional axonal transport in time- and concentration-dependent manners without affecting the neurite diameter [ 16 ]. NTP alleviated oxaliplatin-induced apoptosis via the apoptosis signal regulating kinase 1 (ASK1)-p38 signaling pathway in dorsal root ganglion neurons by inducing thioredoxin [ 19 ]. A T-2 mapping study demonstrated that NTP administration improved knee pain in osteoarthritis without affecting the intra-articular proteoglycan concentration [ 18 ].…”
Section: Introductionmentioning
confidence: 99%